CHARACTER-BASED CLASSROOM MANAGEMENT: IMPLICATIONS FOR POSITIVE STUDENT BEHAVIOR - Rivaldo Paul Telussa; Antonius Awan Asta Adhiprana Whisnubrata; Cristiana Normalita de Lima (EDUCATIONE, 2026)
Classroom discipline problems in lower secondary education often persist when classroom management relies primarily on rules and sanctions rather than value internalization. This study aimed to describe and analyze how character-based classroom management is implemented and how it contributes to improving positive student behavior among Grade VII students at St. Antonius Nabire Middle School (Papua, Indonesia). Using a qualitative descriptive design, data were collected from teachers and Grade VII students through classroom observations, in-depth interviews, and document analysis. Data were analyzed using an interactive qualitative model (data reduction, data display, and conclusion drawing). The findings show that character values—especially discipline, responsibility, and mutual respect—were embedded in classroom rules, learning routines, and daily teacher–student interactions. Consistent teacher role modeling, structured habituation, and positive reinforcement strengthened classroom climate and supported students’ internalization of expected behaviors. Observable changes included improved punctuality and learning discipline, higher responsibility in completing tasks, more respectful peer and teacher interactions, and fewer disruptive behaviors during lessons. Key challenges involved variation in students’ character backgrounds and external environmental influences beyond school. The study concludes that character-based classroom management is a relevant and effective approach for fostering positive behavior in junior high school settings, particularly in under-researched contexts such as Papua. Practically, the findings inform teacher strategies and school policies to standardize value-based class agreements and strengthen school–family collaboration. Future research should employ longitudinal and mixed-methods designs across multiple schools and include family/community perspectives to clarify sustainability and mechanisms of change.